The mediating role of trust in leader in the relations of ethical leadership and distributive justice on internal whistleblowing: a study on Turkish banking sector - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose The purpose of this paper is to explain the effect of perceived ethical leadership and perceived distributive justice on internal whistleblowing intention through trust in leader as a mediator. Design/methodology/approach Following an empirical design, data were collected from 1,296 employees of Turkish financial institutions, located in Istanbul. To test four hypotheses structural equation modelling was applied. Findings Results reveal that trust in a leader fully mediates the positive effects of both ethical leadership and distributive justice on the internal whistleblowing intention. Originality/value This study enhances the understanding of the ethical leadership perception and distributive justice affecting the internal whistleblowing intention in Turkey that is a developing country. Although numerous studies on whistleblowing have been conducted, this study's originality and contribution lay in the examination of trust in the leader as a missing link between the direct relations.
Keywords: Organizational justice; Banking sector; Trust in leader; Ethical leadership; Whistle-blowing intention; Whistleblowing intention; ORGANIZATIONAL JUSTICE; JOB-SATISFACTION; MEMBER-EXCHANGE; TRANSFORMATIONAL LEADERSHIP; TURNOVER INTENTION; MODERATING ROLE; FIT INDEXES; BEHAVIOR; IMPACT; RETALIATION